MORPHOLOGICAL PROPERTIES OF HURA CREPITANS L. (EUPHORBIACEAE) AS PROSPECTIVE RESOURCE FOR PULP AND PAPERMAKING (FUDMA JOURNAL OF SCIENCES, 2021)
Hura crepitans L. (Euphorbiaceae) is a tropic tree species that was investigated for pulp and paper characteristics in this study. The diameters of five (5) different stands of Hura crepitans trees were first determined using diameter tape. Wood slivers were obtained from sapwood of the trees parallel to grain and at three (3) different positions along the axis, at the base (5%), middle (50%) and top (90%). The wood slivers were macerated in a mixture of equal volumes of glacial acetic acid and hydrogen peroxide at between 80 -100 degrees Celsius for 2 hours. Macerated fibres were washed and used to prepare microscopic slides where 15 fibres were measured per slide. Data recorded was subjected to One-way Analysis of Variance (ANOVA) based on Completely Randomized Design (CRD). Results show that both the primary fibre characteristics and derived characteristics were significantly different at p
Keywords: Wood slivers, Macerated fibres, Glacial acetic acid, Pulp and Paper